تقييم أداء زجاج النوافذ من منظور استهلاك الطاقة الكهربائية - فؤاد خضرة; غيث حمود (Tishreen University, 2018)
إن تنامي الطلب على الطاقة قابله ضعف القدرة التوليدية للطاقة الكهربائية بسب ظروف الحرب في سوريا, وبما أن النوافذ تعتبر وسيلة الاتصال البصري بين داخل المبنى وخارجه ومصدر التهوية والإنارة الطبيعية, وبالتالي ذات تأثير مهم على الأداء الحراري للمبنى مما يؤثر على استهلاك الطاقة. من هنا اعتمد البحث على اقتراح بدائل لأنواع زجاج مختلفة وذلك لاختبار الأداء الحراري لها, وقد اعتمد في اختيار البدائل على التنوع بين قيم نفاذيته للإشعاع الشمسي ونفاذيته للضوء المرئي إضافة لتعداد الطبقات, وقد اعتمد لهذه الغاية أسلوب المحاكاة الحاسوبي وتمت مقارنة النتائج بنموذج قياسي (المفرد الشفاف). لقد أظهرت نتائج المقارنة إن مقدار الوفر في استهلاك الطاقة قد يصل إلى 35% لنسب تزجيج عالية بالنسبة للواجهات المعرضة للشمس مباشرة, وذلك بتقليل نفاذية الزجاج الإجمالية للإشعاع الشمسي وزيادة نفاذيته للضوء المرئي لزيادة كمية الإضاءة الطبيعية, مضافاً إليه اعتماد نظام التزجيج متعدد الطبقات, وقد أوصت الدراسة بمراعاة اختيار الزجاج المناسب في مرحلة التصميم المبكرة. The demand growing of energy is offset by the weakening of the generating capacity of power due to the war conditions in Syria. As the windows are the means of optical communication between inside and outside of the building, the source of the ventilation and the natural lighting, thus having an important effect on the thermal performance of the building, which affects the consumption of energy. so the search relied on proposing alternatives for glass to test its thermal performance, the choice of alternatives was based on the diversity between the values of solar radiation permeability and the visual light in addition to enumeration of the layers, to which end the computer simulation method was adopted and the results were compared to a model Standard (single-transparent). The results of the comparison showed that the amount of energy saving could be as high as 35% for the face of the sun-exposed facades directly. By reducing the permeability of the total glass of solar radiation and increasing the permeability of the visible light to increase the amount of natural illumination, plus the adoption of a Multi-layered glazing system , the study recommended that appropriate glass selection must be taken into account in the early design phase